Thematic Learning for Children with Special Needs at Inclusion School During the Covid-19 Pandemic - Tri Nanda Maulidyah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study discusses thematic learning for children with special needs which is carried out online or online learning which is part of distance learning with contemporary special methods that consciously combine internet-based technologies to support the success of students in learning even though it is done remotely. far. As for the benefits of implementing inclusive education for both children with special needs and normal children, they will learn to interact and help each other, teach students that there is no difference and we are all the same. In order to carry out thematic education for children with special needs to the fullest. For this reason, knowing the thematic learning abilities of students with special needs online is very important although basically it is not easy to implement because it requires special supervision from both parents and other families who are at home. Inclusive education does not discriminate in educating normal and abnormal children. Thus, the characteristics of inclusive schools are, among others: having physical accessibility and non-physical accessibility, which aims to maximize services for all children.